2015
DOI: 10.1017/s0967199415000027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of BPA and BPAF on oocyte spindle assembly and polar body release in mice

Abstract: Bisphenol AF (BPAF), a homolog of bisphenol A (BPA), is a widely used environmental chemical that has adverse effects on reproduction. The aim of this study was to analyse the effects of BPA and BPAF exposure on oocyte maturation in vitro. Oocytes were cultured in the presence of BPA or BPAF (2, 20, 50 or 100 μg/ml) for 18 h. At concentrations of 50 and 100 μg/ml, BPA and BPAF inhibited oocyte maturation, with BPAF treatment causing a sharp decrease in the number of oocytes reaching maturity. Oocytes were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
(63 reference statements)
1
27
0
2
Order By: Relevance
“…However, it was only possible to determine whether these effects were attributable to a slowing of the cell cycle or meiotic maturation blockade after culture was prolonged beyond 48 h. Significantly, a proportion of oocytes exposed to BPS remained in the MI or anaphase I/telophase I stages. Therefore, BPS not only causes a slowing of pig oocyte maturation in vitro , similar to that observed during the maturation of mouse oocytes in the presence of BPA 26 or bisphenol AF 27 , but BPS also permanently blocks the course of maturation in a significant portion of oocytes. Similar effects have been observed for the maturation of pig oocytes in BPA presence 24 .…”
Section: Discussionmentioning
confidence: 53%
“…However, it was only possible to determine whether these effects were attributable to a slowing of the cell cycle or meiotic maturation blockade after culture was prolonged beyond 48 h. Significantly, a proportion of oocytes exposed to BPS remained in the MI or anaphase I/telophase I stages. Therefore, BPS not only causes a slowing of pig oocyte maturation in vitro , similar to that observed during the maturation of mouse oocytes in the presence of BPA 26 or bisphenol AF 27 , but BPS also permanently blocks the course of maturation in a significant portion of oocytes. Similar effects have been observed for the maturation of pig oocytes in BPA presence 24 .…”
Section: Discussionmentioning
confidence: 53%
“…BPA exposure suppressed polar body release in mice [31], and exposure to BPA during in vitro oocyte maturation could decrease oocyte quality in Bos taurus [32]. In addition, there was a dose-response association of BPA exposure as for altering the maturation of human oocytes in vitro [22].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that similar with other models, BPA had directly toxic effects on porcine oocytes in vitro , but not DEHP. In mice, oocytes exposed to high doses of BPA experienced a cell cycle delay, and managed to progress to MII when the culture period was prolonged [31]. And short exposure to BPA during the final stages of oocyte maturation is associated with cell cycle delays and spindle abnormalities [17, 22, 33].…”
Section: Discussionmentioning
confidence: 99%
“…However, the limited data from reproductive and other tissues provide preliminary evidence that, like BPA, other bisphenols induce developmental effects ([7375]; reviewed in Rochester and Bolden [76]). For example, BPS and BPF exposure exert effects similar to those reported for BPA on testis gene expression and steroidogenesis in male rats (77); BPAF exposure disrupts mouse oocyte maturation to a similar or greater extent than BPA (42); studies in zebrafish show that the effects of BPS on the reproductive neuroendocrine pathway are similar to BPA (78). However, as with BPA, the nature of the specific effects of exposure undoubtedly depends on the developmental timing of exposure and the tissue examined.…”
Section: Bpa-free: New Problems Not Solutionsmentioning
confidence: 89%
“…The first reported effect of BPA on the oocyte was of an exposure to the periovulatory follicle and an effect on meiotic chromosome alignment and segregation that increased the incidence of chromosomally abnormal eggs in mice (7). Numerous subsequent studies (reviewed in Peretz et al [16] and see [4244]) have provided support for the detrimental effects of BPA on oocyte maturation. Thus, there is ample evidence that the periovulatory oocyte in a range of species—including humans—is vulnerable to the effects of BPA exposure.…”
Section: The Ovary: Vulnerability At Multiple Stagesmentioning
confidence: 99%